Evaluating vehicle emissions inspection and maintenance programs (National Academy Press, 2001)
Emissions inspection and maintenance (I/M) programs subject vehicles to periodic inspections of their emission control systems. Despite widespread use of these programs in air-quality management, policy makers and the public have found a number of problems associated with them. Prominent among these issues is the perception that emissions benefits and other impacts of I/M programs have not been evaluated adequately. Evaluating Vehicle Emissions Inspection and Maintenance Programs assesses the effectiveness of these programs for reducing mobile source emissions. In this report, the committee evaluates the differences in the characteristics of motor vehicle emissions in areas with and without I/M programs, identifies criteria and methodologies for their evaluation, and recommends improvements to the programs. Most useful of all, this book will help summarize the observed benefits of these programs and how they can be redirected in the future to increase their effectiveness.